Improving Secondary School Geography Students' Positive Attitude Towards Map Reading Through Computer Simulation Instructional Package in Bida, Niger State, Nigeria - O.C. Falode; H. Usman; S.C. Ilobeneke; H.A. Mohammed; A.J. Godwin; M.A. Jimoh (University of Sofia, 2016)
This study investigated effectiveness of computer simulation instruction on the attitude of geography students towards map reading in Bida, Nigeria. It also examined the influence of gender on students attitude. The research was a quazi-experimental design. Intact classes of 160 senior secondary school class two students were drawn from two purposively selected secondary schools within Bida and were randomly assigned to experimental and control groups. The experimental group (82 students) was exposed to computer simulation instructional package (CSIP) while their counterparts in the control group (78 students) was taught the same concept of map reading using lecture method. Attitude questionnaire named QGSAMR was used for data collection. The releaibility coefficient of 0.83 was obtained using Cronbach alpha formula. The QGSAMR was administered to students as pretest and post‐test. The students pretest and posttest attitude scores were analyzed using t‐test statistics. The results indicated that there was significant difference between the attitude scores of the two groups in favour of students exposed to computer simulation instructional package. The result however indicated that there was no significant difference between the attitude of male and female students exposed to the package. It was therefore recommended among others, that, computer simulation instructional package should be adopted in teaching and learning of geography as the package would help to improve students attitude towards geography and in turn leads to improved performance.